From structural analysis to observer-based residual generation for fault detection - Pröll, Sebastian; Lunze, Jan; Jarmolowitz, Fabian (Zielona Góra: Uniwersytet Zielonogórski)
This paper combines methods for the structural analysis of bipartite graphs with observer-based residual generation. The analysis of bipartite structure graphs leads to over-determined subsets of equations within a system model, which make it possible to compute residuals for fault detection. In observer-based diagnosis, by contrast, an observability analysis finds observable subsystems, for which residuals can be generated by state observers.
Keywords: fault diagnosis; structural analysis; observer-based diagnosis; diagnosability analysis